Ichthyosis congenita, harlequin type: A case report and a brief review of literature - Veeresh V Dayavannavar; Soumya Jagadeesan; Shashidhar Veerappa; Anees Aisha (Wolters Kluwer Medknow Publications, 2016)
Harlequin ichthyosis (HI) is the most severe type of congenital ichthyosis, and it is extremely rare. It is inherited in an autosomal recessive fashion. Although previously thought to be lethal, recently there have been increased reports of prolonged survival, following improved supportive care and judicious use of systemic retinoids. We report a new case of HI in an infant born of a consanguineous marraige who succumbed on the 5th day of birth despite intensive supportive care, a short review of literature regarding the condition is also presented.